Karakteristik Gelombang Stoneley dalam Menentukan Permeabilitas Reservoir Sumur Pemboran - Kosim Kosim (Department of Physics Education, Universitas Mataram, 2015)
In-situ permeability is an important factor in determining whether an economical drilling oil wells to be mined. Therefore, the calculation in determining the true value of permeability with an attempt to take a further decision, whether the industry is continued or not. Research through study literature is obtained a mathematical modeling from Matheu and Toksoz's work which contains the components of acoustic wavesattenuation factor and rock permeability factor. Furthermore, by combining some of the concepts and theories, mathematical models are used for acoustic field data logs and other data which are required to get permeability. Data from the acoustic log is analyzed to determine the time delay for P, S and Stoneley waves, then determination of the speed, frequency and attenuation factor, especially for wave Stoneley. In this permeability calculations, it is assumed that the condition of the rock formations in the area of measurement is a permeable rock and contains fractures. The results show that the permeability in measurement area at a depth position indicates suitable with the data of rock state.